Tailoring the magnetic properties and microstructure of Alnico 8 magnets by various Ti contents and processing conditions. (April 2022) - Rehman, Sajjad Ur; Wei, Chen; Zhang, Ruibiao; Liu, Haihua; Li, Shaoxiong; Minglong, Zhong; Yang, Munan; Jiang, Qingzheng; Wang, Jun; Zhong, Zhenchen
Abstract: Shape anisotropy, developed as a result of spinodal decomposition (SD) is the basis for the hysteresis behavior of Alnico magnets. The SD process is sensitive to processing conditions and constituent elements. In this paper, the development of spinodal structure and its effects on magnetic properties and serviceability of Alnico 8 alloys are investigated. The Ti-content is varied between 2.5 and 7.5 wt%. The magnets are fabricated by conventional casting, homogenization, magnetic field annealing and tempering treatments. The magnetic properties of intrinsic coercivity, H cj  = 30 kA/m, remanence, B r  = 0.53 T and maximum energy density, (BH) max  = 6.03 kJ/m 3 for 2.5 wt% Ti are increased to H cj  = 150 kA/m, B r  = 0.0.88 T and (BH) max  = 29.3 kJ/m 3 for 6.5 wt% Ti alloy. These magnetic properties are 100% reversible up to 800 K. Furthermore, an alloy with 5.5 wt% Ti is directionally solidified and magnetic properties of B r  = 1.01 T and (BH) max  = 58.9 kJ/m 3 are obtained. The evolution of mosaic nano structure, the mechanism of magnetic hardening and the interactions of various phases have been investigated. Highlights: Alnico 8 alloys are fabricated by various processing conditions and by changing the content of most reactive element in the alloys, Ti. The alloys are treated in magnetic field of 2 T/1108 K to develop mosaic nanostructure. The best magnetic properties are obtained in the directionally solidified alloys whereby both the micron sized grains and nano rods aligned in the same direction. 100% magnetic property reversibility is observed up to 800 K. Recoil curves are analyzed to investigate the serviceability of the alloys.